Determination of the optical properties of two-layer turbid media from spatially resolved reflectance measurements in the frequency domain - Alexandrakis, George (My University, 2000)
Quantification of the optical properties of superficial biological tissue (e.g. skin on muscle) from spatially resolved reflectance measurements can yield important physiological information. Some examples include the non-invasive measurement of chemotherapy drugs or exogenous chromophores used for photodynamic cancer treatment and the assessment of hemoglobin oxygenation in tissue. Superficial tissue is a multilayered structure with each component having different macroscopic absorption and scattering coefficients, as well as different vascularization and exogenous chromophore pharmacokinetics. A layered model of photon transport is therefore required to match theoretical predictions with experimental measurements. Once a photon transport model is developed, it defines the forward calculation used in the inverse problem of determining the set of tissue optical properties that gives the best fit to experimental data. In the present work the frequency domain (FD) method is employed to probe a two-layer turbid medium. The goal is to improve quantification of superficial tissue optical properties relative to current methods assuming tissue homogeneity. Chapter 2 introduces simulated annealing as a robust method of exploring the limits of a two-layer pure diffusion model in determining the optical properties of a two-layer turbid medium. The inadequacies of pure diffusive transport lead to inaccurate optical property estimates for the top layer. To improve on these estimates a hybrid Monte Carlo (MC)--diffusion model for FD photon transport was developed and presented in Chapter 3. The hybrid model was shown to accurately model MC simulated reflectance data for all optical properties in the physiological range. In Chapter 4 an efficient hybrid simplex--simulated annealing global optimization algorithm was introduced to demonstrate that the hybrid transport model can, in principle, accurately determine all optical properties of a two-layer turbid medium. The practical feasibility of the method was tested with high accuracy FD experimental measurements. Some preliminary results and future directions towards the in vivo implementation of the method are discussed.
Keywords: medical physics